Technology adoption and social media marketing performance of small and medium enterprises - Okwudiri, Nnanna-Ohuonu; Oliseh, Peter Sunday; Anagwu, Victoria Kenechukwu; Nwanya , Christian Chidi; Chukwu , Chinedumathew (goodwood publishing, 2025)
Purpose: This study examined how small and medium-sized businesses (SMEs) in Sub-Saharan Africa (SSA) use technology, and how well they perform on social media marketing. The objectives of the study were to determine the most suitable methods for evaluating the digital competence of SMEs to achieve customer engagement, and to evaluate the challenges SMEs face in acquiring digital competence for enhanced customer engagement among Sub-Saharan SMEs. Methods: The study synthesized findings from existing academic literature published between 2015 and 2025 using a qualitative research design that included a systematic literature review and thematic content analysis. Results: The findings revealed that assessing employees' perceived usefulness and ease of use of digital tools, evaluating performance metrics related to customer engagement, and analyzing investment in digital training are suitable methods for evaluating digital competence. The study also identified significant challenges, including a lack of necessary digital skills, financial constraints, inadequate technological infrastructure, and low digital literacy. Limitations: The generalizability of the this study is limited because of using only qualitative analysis. Also, focusing on a single source of data (secondary qualitative) which may have context specific issues limited this study also. Contribution: Given that technology in marking is a very significant area in the management and sustainability of organizations, especially SMEs to be able to compete with bigger and more established businesses, this study makes a case for social media marketing integration into the operations of SMEs, and ways to evaluate their digital competence so as to achieve customer engagement.